NAD+ Attenuates Bilirubin-Induced Hyperexcitation in the Ventral Cochlear Nucleus by Inhibiting Excitatory Neurotransmission and Neuronal Excitability - Liang, Min; Yin, Xin-Lu; Wang, Lu-Yang; Yin, Wei-Hai; Song, Ning-Ying; Shi, Hai-Bo; Li, Chun-Yan; Yin, Shan-Kai (Frontiers in Cellular Neuroscience, 2017)
Nicotinamide adenine dinucleotide (NAD+) is an important molecule with extensive biological functions in various cellular processes, including protection against cell injuries. However, little is known regarding the roles of NAD+ in neuronal excitation and excitotoxicity associated with many neurodegenerative disorders and diseases. Using patch-clamp recordings, we studied its potential effects on principal neurons in the ventral cochlear nucleus (VCN), which is particularly vulnerable to bilirubin excitotoxicity. We found that NAD+ effectively decreased the size of evoked excitatory postsynaptic currents (eEPSCs), increased paired-pulse ratio (PPR), and reversed the effect of bilirubin on eEPSCs, implicating its inhibitory effects on the presynaptic release probability (Pr). Moreover, NAD+ not only decreased the basal frequency of miniature EPSCs (mEPSCs), but also reversed bilirubin-induced increases in the frequency of mEPSCs without affecting their amplitude under either condition. Furthermore, we found that NAD+ decreased the frequency of spontaneous firing of VCN neurons as well as bilirubin-induced increases in firing frequency. Whole-cell current-clamp recordings showed that NAD+ could directly decrease the intrinsic excitability of VCN neurons in the presence of synaptic blockers, suggesting NAD+ exerts its actions in both presynaptic and postsynaptic loci. Consistent with these observations, we found that the latency of the first postsynaptic spike triggered by high-frequency train stimulation of presynaptic afferents (i.e. the auditory nerve) was prolonged by NAD+. These results collectively indicate that NAD+ suppresses presynaptic transmitter release and postsynaptic excitability, jointly weakening excitatory neurotransmission. Our findings provide a basis for the exploration of NAD+ for the prevention and treatment of bilirubin encephalopathy and excitotoxicity associated with other neurological disorders.